The Laxford shear zone: an end-Archaean terrane boundary? - Goodenough, K.; Park, R.; Krabbendam, M.; Myers, J.; Wheeler, J.; Loughlin, S.; Crowley, Q.; Friend, C.; Beach, A.; Kinny, Peter; Graham, R. (Geological Society Publishing House, 2010)
The Lewisian Gneiss Complex of northwestern Scotland consists of Archaean gneisses, variably reworked during the Proterozoic. It can be divided into three districts – a central granulitefacies district between districts of amphibolite-facies gneiss to the north and south. Recent work has interpreted these districts in terms of separate terranes, initiating a controversy that has implications for how Precambrian rocks are understood worldwide. The northern district of the Lewisian Gneiss Complex (the Rhiconich terrane) is separated from the central district (the Assynt terrane) by a broad ductile shear zone known as the Laxford Shear Zone. This paper reviews the geology of the Laxford Shear Zone, clarifying field relationships and discussing other evidence, to consider whether or not it does indeed represent a terrane boundary. A detailed review of field, geochemical and geochronological evidence supports the recognition of the separate Assynt and Rhiconich terranes. Mafic dykes (the Scourie Dyke Swarm) and granitoids, of Palaeoproterozoic age, occur on both sides of the Laxford Shear Zone and thus the terranes were most probably juxtaposed during the late Archaean to early Palaeoproterozoic Inverian event. Subsequently, the less-competent, more-hydrous amphibolite-facies gneisses of the Rhiconich terrane were affected by later Palaeoproterozoic (Laxfordian) deformation and partial melting, to a greater extent than the morecompetent granulite-facies gneisses of the Assynt terrane.